Isolation and Detection of Antibiotic Sensitivity Pattern of Escherichia coli from Ducks in Bangladesh and Nepal (Microbes and Health, 2013)
A total of 120 rectal swab samples from ducks (sixty samples from Nepalgunj area of Nepal and 60 from Boyera area under Mymensingh district of Bangladesh) were collected for the isolation of Escherichia coli and their antibiogram study. After cultural and biochemical examination, a total of 40 samples from Nepalgunj and 45 samples from Boyera were found positive for E. coli. Pathogenicity study of 10 positive isolates from Nepalgunj and 12 positive isolates from Boyera were done to detect the presence of enterotoxin. All inoculated mice died showing typical lesion of extensive hemorrhage and massive edema. The isolates from two different origins showed major difference in their antibiogram study. The isolates of Nepal were highly sensitive to ciprofloxacin, co-trimoxazole, chloramphenicol and amoxicillin; moderately sensitive to nalidixic acid and; less sensitive to kanamycin and resistant to cephalexin. However, the isolates of Bangladesh were highly sensitive to ciprofloxacin, chloramphenicol and amoxicillin; moderately sensitive to nalidixic acid, cephalexin, and co-trimoxazole; less sensitive to kanamycin. This variation of antibiotic sensitivity and resistance patterns among the E. coli isolates of Nepal and Bangladesh might be due to strain variations and indiscriminate use of antibiotics in these two different countries.DOI: http://dx.doi.org/10.3329/mh.v1i1.13704 Microbes and Health Vol.1(1) June 2012 pp.6-8